THE ANALYSIS TOWARDS STATE APPARATUS COMMISSION ROLE IN ASN MANAGEMENT SYSTEM IN INDONESIA - Ajib Rakhmawanto (Faculty of Law, Universitas Jenderal Soedirman, 2015)
In administrating bureaurcy business process, professional state apparatus are needed. Law number 5 of 2014 about the state civil apparatus mentions management based on merit that supposed to be supervised by an independen institution: State Apparatuss Commision (KASN). This article aims to analyze the KASN, and identify its task, function, and responsibilities. The analysis showed that KASN was formed to create professional state apparatus and supervise the merit system based management. The function of KASN becomes ineffective considering there is NCSA, an establish body with a role to supervise the ASN management. KASN will cause an overlapping and conflict of interest between the two institutions. Key words: State Apparatus Law, government institution, KASN